5A 5Aรูปแบบการเรียนรู้เพื่อพัฒนาบัณฑิตไทยสู่สากล: รูปแบบการเรียนรู้ - จารุพันธ์, สารดา (FOYER: The Journal of Humanities, Social Sciences, and Education, 2020)
At this disruptive moment of the world, stakeholders in Thai educational sectors need to find ways to develop Thai graduates to be qualified for global workforce markets. This article presents details of a research constructed with an attempt to instill skills needed for 21st Thai learners with a research tool entitled ‘5A learning Portfolio”. Theories of English for specific purposes with two key learning strategies; self-directed learning and metacognition in language learning, are integrated to foster Thai engineering students to be aware of the skills through the record of their learning portfolio with the proposed model ‘5A’. The research objectives aim to investigate the effectiveness of the proposed tool used with 30 third-year Engineering students enrolled the English writing course in a Thai university and to find out their perceptions on the use of the learning model. Data was gathered through the intervention of the course lesson plan integrated with the ‘5 A learning portfolio’, pre-test-post test, the rubric and questionnaire and analyzed by percentage, arithmetic means, standard deviation and t-test. . The findings show the effectiveness of the technique through the higher learning achievement in the post test of the target group at the .05 level of statistic significance. The perceptions of the users also showed the positive awareness of the strategies.This learning tool is introduced for teachers to use and adjust for their learners of other settings aiming to develop Thai learnersas 21st qualified graduates. Keywords:5A Learning Portfolio, Develop Thai learners for 21st, English for specific purposes, Self-directed learning Strategy, Metacognition in language learning,